Enhanced performance of EFG silicon solar cells by using vapor texturing process. (May 2015) - Han, Kyu-Min; Cho, Jun-Sik; Yoo, Jinsu
Abstract: Surface texturing of silicon (Si) wafer is an effective and more lasting technique for improving the conversion efficiency of solar cells by improving light trapping effects compared to hydrogenated silicon nitride (SiNx :H) antireflection (AR) coatings. In this paper, we present the method of vapor texturing for achieving a very low reflectance of edge-defined film-fed growth (EFG) Si surface. Prior to vapor texturing, silicon wafers were textured by alkaline (NaOH) and mixed acidic (HF, HNO3 and DI water) solutions to investigate a uniformly textured surface. Also, we carried out vapor texturing for achieving the minimum reflectance by uniform and homogeneous surface morphology following surface texturing optimized by alkaline or acidic solutions. Using the optimum process conditions, EFG Si solar cell showed conversion efficiency, fill factor, short circuit current density and open circuit voltages as high as 14.1%, 74.7%, 32 mA/cm 2 and 588 mV, respectively. Highlights: Surface texturing of Si wafer is effective in light trapping for improving solar cell efficiency. Before vapor texturing, the EFG Si was textured by alkaline and acidic solutions to optimize the surface structure. Porous structure on EFG Si surface generated by vapor texturing. We study on a vapor texturing technique for EFG Si surface morphology.